Ipsilateral femoral neck and shaft fractures fixation with proximal femoral nail antirotation II (PFNA II): technical note and cases series - Wu, Kuen-Ting (J Orthop Surg Res, 2020)
BACKGROUND: Combined ipsilateral femoral neck and shaft fractures are an uncommon type of fractures. A number of different implant options are available for the management of this injury. Two-device procedures were suggested because of the higher rate of malunion by single-device treatment. However, surgical treatment using a cephalomedullary nail is still an alternative option that provides better mechanical advantage and minimal invasion. This study details the technique of treating these pattern fractures with proximal femoral nail anti-rotation II (PFNA-II) to achieve an acceptable reduction in both fracture sites. METHODS: Ten cases of ipsilateral femoral neck and shaft fractures under reduction by PFNA II were included and reviewed. A saw-bone model was also utilized to perform the detailed technique of reduction and fixation of PFNA II. RESULTS: Under the special technique by using the PFNA II, all ten cases achieved optimal reduction and alignment of both fracture sites in intra-operative fluoroscopy. There was no intra-operative complication noted. After 6 months of follow-up, radiography revealed proper alignment and well union of the fractures. CONCLUSIONS: Fixation of ipsilateral femoral neck and shaft fractures with a single construct provides advantages of good biomechanical function, minimal invasion, reduced blood loss, and less operation time when comparing to two-device fixation. Thus, if acceptable reduction could be achieved, fixation by one PFNA II was a good alternative choice for this injury pattern.